Lightweight Design and Production Practice of the Heavy Truck Drive Axle - Yan Xiaolou; Qiu Yang; Li Youli (Jixie chuandong)
In order to optimize the structural performance of the heavy truck drive axle and realize the market supply goal of the whole axle lightweight, the corresponding research is carried out based on CAE/CAM technology. Using the systematic layout thinking, the mathematical model is scientifically built, a complete lightweight design axle is formed through CAE simulation analysis and CAM collaborative production, and the prototype test is conducted. The results show that the weight of the whole axle after the lightweight design is relatively reduced by 12.7% and the transmission efficiency is more than 95% on the premise of meeting the key performance parameters such as noise limit and B10 life. This design method and thinking can provide reference ideas for the improvement of other parts of heavy trucks, especially in the field of the lightweight research, and it would have great application and promotion prospects.